An embryological surprise in the inguinal canal: Deep epidermoid cyst mimicking spermatic cord pathology – A case report - MARY BABY, NIKITA (Indian Journal of Case Reports, 2026)
Epidermoid cysts are common benign lesions that typically arise from the skin and subcutaneous tissues; however, deep-seated inguinal epidermoid cysts are rare and may mimic spermatic cord pathology on imaging. We report a 23-year-old male presenting with left inguinal pain and swelling of 2-week duration. Magnetic resonance imaging demonstrated a well-defined cystic lesion along the spermatic cord showing T1 and T2 hypointensity, diffusion restriction, and no post-contrast enhancement, raising suspicion for an infected encysted hydrocele or spermatic cord abscess. Surgical exploration revealed a well-encapsulated deep inguinal cyst, which was excised completely. Histopathology confirmed an epidermoid cyst. This case highlights a diagnostic pitfall where diffusion restriction may mimic infection and emphasizes the importance of considering epidermoid cyst in the differential diagnosis of non-enhancing inguinal lesions.